Temporal dynamics of the carbonate system in a tropical rhodolith bed from a protected Caribbean bay - Rincón-Díaz, Natalia; Gómez, Carlos E.; Piñeros-Pérez, Valentina; Alvarado-Jiménez, Félix; Núñez, Samuel; García-Urueña, Rocío (Frontiers in Marine Science, 2025)
Coastal zones are key players in the global carbon cycle, yet the temporal dynamics of their carbonate system, particularly in tropical rhodolith habitats, remain understudied. This study assessed seasonal and spatial variability in carbonate chemistry in Gairaca Bay, a protected tropical bay within Tayrona National Natural Park, Colombian Caribbean. Sampling was conducted in 2023–2024 across three habitats: a rhodolith bed (1, 7, 15 m depth), the bay entrance (outer bay, 10 m depth), and a shallow sandy-bottom area (inner bay, 1 and 6 m depths). Temperature, salinity, and total scale pH (pHT) were measured in situ; total alkalinity (TA) was determined via open-cell titration, and dissolved inorganic carbon (DIC), pCO2, bicarbonate (HCO3-), carbonate (CO32-), and aragonite saturation state (Ωarag) were calculated. Seasonal and spatial patterns were analyzed using PERMANOVA. Significant seasonal differences were found in temperature (F = 248.42, p < 0.05), salinity (F = 49.02, p < 0.05), TA (F = 7.65, p < 0.001), and DIC (F = 2.54, p < 0.001), with no significant variation among sites or depths. Upwelling periods were cooler and saltier (25.9 ± 1.14 °C; 34.48 ± 0.46), with elevated TA and DIC, and slightly lower pHT and Ωarag. Non-upwelling periods were warmer (30.0 ± 0.76 °C), less saline (33.36 ± 0.28), and had higher pHT and Ωarag. Seasonal delta analysis indicated greater variability during non-upwelling, linked to enhanced freshwater discharge. The outer bay showed the highest variability in pHT and Ωarag, while the inner bay was most stable for TA and DIC. The rhodolith bed bottom exhibited high TA variability but stability in pHT and Ωarag, especially during non-upwelling. Seasonal processes, including upwelling and freshwater inputs, drive carbonate system variability in Gairaca Bay. The stability of pHT and Ωarag in the rhodolith bed bottom suggests a potential role as a biogeochemical refuge in acidification-prone tropical environments.